Improving Students’ Skills in Writing Descriptive Texts by Using Digital Photographs - Khadijah Maming; Ali Wira Rahman; Amir Patintingan; Devy Anggraini (University of Surakarta, 2023)
In English Learning Teaching (ELT), digital photographs are considered acompelling visual medium to help students write English texts. A writing skillis a capacity to convert ideas into complete, comprehensive and understandablesentences that may be used to convey those ideas to the reader effectively. Thepurpose of this research is to find out whether using digital photographs canimprove students’ skills in writing descriptive texts or not. The researchers useda descriptive quantitative pre-experimental method by applying digital picturesto teach writing descriptive text. The sample of this research consists of thirtystudents at SMP Negeri 1 Pangsid, South Sulawesi. The result shows thatstudents’ writing skills increased by using digital photographs. The results areindicated by the mean value of the pretest (44,73) and the posttest (82,93). Aftercalculating the t-test, the researchers found that the null hypothesis (H0) wasrejected, and the alternative hypothesis (H1) was accepted. Using digitalphotographs as a teaching and learning medium can improve students’ skills nwriting descriptive texts. In other words, this medium eases the students inconstructing their ideas through descriptive essays.